Revitalisasi Kinerja Sumber Daya Manusia Mempengaruhi Produktivitas Organisasi - Prasetyo, Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2020)
Organizations can apply organizational behavior if there are human resources who run it, by the knowledge and abilities possessed. Humans are still vital determinants and controllers of an organization in carrying out its work or business processes so that positive interactions between its human resources and the organizations that shelter it can make a symbiotic relationship of mutualism. Although, in this era of disruption some human roles have been replaced by machines and robotics. To produce and deliver the desired quality of human resources and be able to compete and compete comprehensively and holistically in this global competition. Of course, it takes the ability and knowledge of the organization in its management. Some factors affect organizational productivity to be able to compete and compete in their fields optimally, namely, the revitalization factor of the performance of human resources in the organization. The revitalization process of human resource performance greatly influences the success of organizational productivity in facing challenges and competition in various sectors and as an indicator of the existence of the organization in the future. Success and failure in the process of revitalizing the performance of human resources depend on the extent to which the organization treats its human resource assets. A good organization will always update and upgrade all the needs of its human resource assets to be able to provide complete services and become a productive, effective organization that has an output value both in quality and quantity